CONCEPT MAP, SOME TERMINOLOGIES OF THE STUDY OF FAITH, AND THE SCOPE OF THE STUDY OF AKIDAH AKHLAK - Sitti Isni Azzaah; Ira Suryani (Universitas Dharmawangsa, 2021)
ABSTRAC The purpose of this research is to be able to find out what creed, morals, and creeds are, as well as various creeds and morals, and research using library research that is supported based on book sources, and the results of the research are creed will be formed. if we believe and believe in Allah as the God who has created us, while morals will be formed if we prepare ourselves to do good so that faith and morality are not related to each other if the faith alone is not good then the morals are also not good, then both must be able to be reconciled. together in a balanced manner, namely with a strong creed and good morals.